KEARIFAN LOKAL MASYARAKAT DESA ADAT SADE DALAM MENGHADAPI COVID-19 - Nur Arning Tengara Kasih; Renny Nurhasana (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
Local wisdom of indigenous village communities can be interpreted as ideas, principles of life, behavior, rules or norms, taboos, and punishments derived from the experience of hereditary ancestors, one of which is to deal with life problems, namely disasters. COVID-19 is a disaster that causes difficult conditions to arise in society because it has an impact on all aspects of life. Therefore, people should fight against not only COVID-19 virus attack, but also food scarcity, and hunger. This study refers to the theory of local knowledge suggested by Geertz (1983) stating that local knowledge is born from experiences that have been passed in dealing with disasters and is knowledge owned by local communities and managed locally, in which there is a